Sustaining Pre-Service Teachers’ Virtual Engagement in a Health Education Course through Interactive Buzz Sessions - Dizon, Stephanie G.; Fernandez, Paula Mae Q.; Dalangin, Harold Raven S.; Mungcal, Kervy S.; Tolentino, Julius Ceazar; Valenzuela, Luwy R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Distance learning manifested an increasing growth in the field of higher education. Although it may not be exactly comparable to a residential face-to-face encounter, considering the engagement of the students in learning within a virtual context is still significant. Thus, this action research was conducted to sustain the level of virtual engagement among undergraduate teacher education students specializing in Physical Education when interactive buzz breaks are introduced in their online synchronous sessions. This study utilized a mixed-method collaborative action research approach. The participants included 48 second-year Bachelor of Physical Education (BPEd) students enrolled in the course, “Drug Education, Consumer Health, and Nutrition”, from a teacher education institution (TEI) in Central Luzon, Philippines during the second semester of the academic year 2021-2022. Multiple sources of data were collected and analyzed which included teacher’s observation notes, Student Engagement Survey Questionnaire, and reflective journals. Five (5) interactive buzz break activities were implemented using the “Wordwall” as an intervention within twelve synchronous sessions. The survey questionnaire was administered before (pre-assessment) and after (post-assessment) the intervention to describe the students’ level of virtual engagement. Results of the quantitative phase revealed that there is a high level of students’ behavioral, cognitive, and emotional virtual engagement before and after the strategy. The qualitative phase further promoted these results to reveal the remarkable experiences encountered by students during the intervention implementation that contributed to sustaining their virtual engagement. The derived results and findings posit that administering various interactive buzz break activities with the utilization of various educational platforms synchronously and asynchronously may sustain and further improve students’ virtual engagement.